2013
DOI: 10.1177/0269881113493364
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of reformulated OxyContin® tablets: assessing comparative preferences and tampering potential

Abstract: Reformulated OxyContin® (oxycodone HCl controlled-release or ORF) was developed as a tamper and abuse-deterrent product, to reduce the risk of product abuse, misuse and their consequences. This noninterventional single-session study asked participants who were medically-healthy recreational opioid users, aged 18 years and older, to consider how they would use commonly available supplies to tamper with placebo ORF and placebo original OxyContin (OC) tablets, and how they would assess the attractiveness of tampe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 30 publications
1
35
0
Order By: Relevance
“…Studies have shown that it is less attractive to recreational drug abusers than the original extended-release formulation. [101,102] Targiniq™ ER (Purdue Pharma LP) was approved in the USA in July 2014. This abuse-deterrent formulation contains oxycodone combined with naloxone -an antagonist that blocks the euphoric effects of oxycodone if the tablet is crushed for snorting or manipulated for injection.…”
Section: Differences In Routes Of Abuse Between Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that it is less attractive to recreational drug abusers than the original extended-release formulation. [101,102] Targiniq™ ER (Purdue Pharma LP) was approved in the USA in July 2014. This abuse-deterrent formulation contains oxycodone combined with naloxone -an antagonist that blocks the euphoric effects of oxycodone if the tablet is crushed for snorting or manipulated for injection.…”
Section: Differences In Routes Of Abuse Between Populationsmentioning
confidence: 99%
“…[94][95][96][97][98][99] A growing body of evidence suggests that introduction of the abuse-deterrent formulation of oxycodone has been associated with decreased rates of abuse and diversion of this opioid analgesic in the USA. [101,[110][111][112][113][114][115][116][117][118][119]. Cost savings have also been reported to be associated with reductions in abuse following the introduction of the abuse-deterrent reformulation of oxycodone in the USA.…”
Section: Differences In Routes Of Abuse Between Populationsmentioning
confidence: 99%
“…For example, an easily crushed opioid formulation that can be readily prepared for injection within minutes is likely to be preferred over a hardened tablet that resists extraction and takes considerable effort and time to manipulate. In a previous study, 40.0% to 53.3% of participants (experienced users of opioids for nonmedical purposes) stated that they were willing to spend a maximum of 10 minutes tampering with oxycodone (10 or 40 mg) (9). A comparison of two formulations of oxymorphone found that the maximum time participants were willing to spend tampering with the products was approximately 15 minutes (10).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Category 1 studies that focus on the "output" of the manipulation effort, the ALERRT instrument was developed to capture information about the "input" (time, effort, and resources necessary to convert the product into an abusable form). If the degree of effort required is perceived by drug users to be onerous, it is possible that this property may in and of itself deter abuse (9,11). In this respect, it is important to note that this dimension is not captured in Category 3 clinical studies designed to evaluate the abuse potential of a new drug.…”
Section: Introductionmentioning
confidence: 99%
“…Early US studies indicate lower levels of misuse (Havens et al, 2014), attractiveness (Sellers et al, 2013) and street price (Severtson et al, 2013) amongst specific populations and a decrease in OxyContin ® poisonings following introduction of the reformulated product (Severtson et al, 2013). A reduction in national sales of the reformulated product has also been observed (Hwang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%